S115 The effect of posture on the 2nd intercostal space surface parasternal electromyogram (EMGpara): validating a novel clinical tool to measure neural respiratory drive. (2nd December 2011) - Ramsay, M C; Suh, E-S; Mandal, S; Murphy, P; Steier, J; Simonds, A; Hart, N
Abstract : Introduction: Although neural respiratory drive (NRD), as measured by diaphragm EMG, has been shown to reflect the balance between the respiratory muscle load and capacity providing a marker of disease severity, it requires insertion of an oesophageal catheter which limits its clinical utility. 2nd intercostal space surface EMGpara has been shown to be a useful alternative non-invasive monitoring tool in acute COPD (Murphy et al. Thorax 2011;66 :602–8) and overnight in asthmatic patients (Steier et al. Thorax 2011;66 :609–14). Previous data has suggested that there is reduced activation of the chest wall muscles in normal subjects in the supine posture as a consequence of a change in chest wall configuration. To assess the clinical utility and validity of EMGpara to continuously monitor changes in NRD, we investigated the effect of different posture on the EMGpara in normal subjects. Methods: Wet gel electrodes were placed at the parasternal edge of the 2nd intercostal space following skin preparation. Signals were amplified and filtered before analogue to digital conversion and digital processing providing the raw signal and root mean squared data. Five positions included sitting at 45 degrees, lying flat, lying on the right and left hand side and sitting at 90 degrees. EMGpara was measured during 2 min of tidal breathing in each posture. Resting EMG signal was normalised to the maximal inspiratory manoeuvres performed in each position (EMGpara%max). Results: Eight healthy subjects were recruited with a mean age 32 years ±2 years; 4 male; BMI 23±2 kg/m 2 . Mean EMGpara%max was 4.60±3.93% sitting at 45 degrees, 4.82±2.27% lying flat, 5.32±3.91% lying on the right hand side, 4.47±4.47% lying on the left hand side, 4.58±3.75% sitting at 90 degrees. A repeated measures ANOVA showed there was no significant difference in EMG para%max between the different postures (p= 0.97; Abstract S115 figure 1 ). Conclusion: NRD, as measured by EMGpara%max, is stable across a range of different postures. It provides comparable information independent of body position and could be considered as a monitoring tool in clinical practice, including for overnight monitoring.